2022
DOI: 10.1007/s11063-022-11112-0
|View full text |Cite
|
Sign up to set email alerts
|

AI Assisted Attention Mechanism for Hybrid Neural Model to Assess Online Attitudes About COVID-19

Abstract: COVID-19 is a novel virus that presents challenges due to a lack of consistent and in-depth research. The news of the COVID-19 spreads across the globe, resulting in a flood of posts on social media sites. Apart from health, social, and economic disturbances brought by the COVID-19 pandemic, another important consequence involves public mental health crises which is of greater concern. Data related to COVID-19 is a valuable asset for researchers in understanding people's feelings related to the pandemic. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Basiri et al suggested a new approach for coronavirus-related tweet emotion categorization by combining four deep learning methods : DistilBERT [27], fast text, BiGRU, and CNN [6]. Large labelled dataset of tweets is used to train the classification models and achieved highest 85.5% accuracy.…”
Section: Organization Of the Papermentioning
confidence: 99%
“…Basiri et al suggested a new approach for coronavirus-related tweet emotion categorization by combining four deep learning methods : DistilBERT [27], fast text, BiGRU, and CNN [6]. Large labelled dataset of tweets is used to train the classification models and achieved highest 85.5% accuracy.…”
Section: Organization Of the Papermentioning
confidence: 99%